UPAYA GURU DALAM MENGATASI KESULITAN BELAJAR MEMBACA DAN MENULIS SISWA KELAS IV DI SDN 41 GELAMAK - Beni; Mujahidin; Eliyah (CV. Adiba Aisha Amira, 2026)
The aim of this research is to reveal: 1) The efforts made by teachers to overcome the difficulties of class IV students in learning to read and write at SDN 41 Gelamak; 2) Supporting factors and inhibiting factors for teachers in overcoming the difficulties of fourth grade students learning to read and write at SDN 41 Gelamak. This research uses a qualitative approach and a phenomenological type of research. Data collection techniques used were interviews, observation and documentation. The data analysis techniques used are data collection, data reduction (data simplification), data presentation (displaying data), and verification (concluding data). The results of the research show that: 1. The efforts made by teachers to overcome the difficulties of class IV students in learning to read and write at SDN 41 Gelamak are as follows: a. Providing additional hours, b. Creating fun learning, c. Provide motivation and encouragement. 2. Supporting factors and inhibiting factors for teachers in overcoming the difficulties of class IV students learning to read and write at SDN 41 Gelamak, as follows: a. Supporting factors such as supportive school facilities and qualified teaching human resources, b. Inhibiting factors include children's lack of concentration, low interest and motivation, and lack of parental attention.